(untitled) (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Accurate knowledge of the Gestational Age (GA) is the key for the good antenatal care and successful deliveries of babies. Menstrual history can be unreliable or misleading at many times. So, there is a need of a parameter for supplementing the gestational age estimation with minimal error. Objective: To find out the role of sonographically measured head circumference for determination of gestational age in 2nd and 3rd trimester of pregnancy. Method: This cross sectional study was carried out on 100 normal pregnant women with apparently normal fetuses between 13 to 42 weeks of gestation referred to the Department of Radiology and Imaging, Bangabandhu Sheikh Mujib Medical University and Dhaka Medical College Hospital for ultrasonic evaluation of pregnancy profile. Fetal head circumference was measured sonographically and gestational age was determined on the basis of BPD, FL and HC. The parameters were corelated with gestationa age determined on the basis of LMP. A p value of <0.05 was taken as level of significance. Result: More than half of the study subjects were in the age group of 21 – 25 years and mean age of the study subjects was 24.6±5.2 years in this study. Maximum study subjects were housewife (65.0%) followed by 19.0% student and 16.0% service holder. A positive correlation was found between the head circumference and gestational age (r=0.991, p <0.001) which is more significant than BPD (r=0.986, p <0.001) and FL (r = 0.989, p< 0.001). Conclusion: Foetal head circumference can be an additional parameter for estimation of the gestational age as it almost corresponds with the gestational age in second and third trimesters.